Endangered Lilium Species of Turkey - Sevim Demir; Fisun Gürsel Çelikel (Turkish Journal of Agriculture: Food Science and Technology)
Turkey, which is among the major gene centers of the world and has a special place in plant genetic diversity. However, many plant genetic resources, including geophytes, are under genetic erosion because of the environmental and other problems and therefore face with the danger of extinction. Lilium ciliatum is endemic to North East Anatolia. IUCN (International Union for the Conservation of Natural Resources) Red List Category of this species is Endangered (EN). Lilium ciliatum naturally grown in Zigana pass, Bayburt, Trabzon, Bulancak, Giresun and Gümüşhane is endangered and major threats of L. ciliatum are road construction and human disturbance related to ecotourism and recreation. It was reported that Lilium carniolicum naturally grown in Turkey is endangered although it isn’t in the IUCN Red List. Distribution areas of L. carniolicum are Trabzon, Rize, Artvin and it is also endemic to North East Anatolia. These species have high potential for use as ornamental plants with their colorful big flowers. In addition, the bulbs of these species are also used in the cosmetic industry and medicine. These are the main properties that increase the importance of L. ciliatum and L. carniolicum species. Therefore it is very important to protect the habitats of these species, ensure the continuity of their generations. The disappearance of these endemic species from our country means to disappear from the world. This review has been given in order to give some information about the endangered Lilium species of Turkey and conservation actions on these species in Turkey flora and take attention to the issue.